Knowledge sharing in the software industry: the importance of an adequate environment - Pinto, Danieli; Damian, Ieda Pelogia Martins [UNESP] (Universidade Federal do Paraná, 2022)
Introduction: sharing is one of the most important knowledge management processes, since knowledge is in people’s minds and it should be externalized in order to be used to create and add value to the organization. Through this process, knowledge is converted from tacit to explicit. Furthermore, to have an adequate organizational environment is essential in order for knowledge management to be effective. This paper aims to investigate how the process of sharing knowledge relates to the software industry environment. Method
Compartilhamento do conhecimento na indústria de software: a importância de um ambiente adequado
Keywords: Knowledge creation; Knowledge management; Organizational environment; Value creation